Insight into the Reactivity Profile of Solid-State Aryl Bromides in Suzuki–Miyaura Cross-Coupling Reactions Using Ball Milling - Kubota, Koji; Kondo, Keisuke; Seo, Tamae; Ito, Hajime (Synlett, 2022)
Despite recent advances in solid-state organic synthesis using ball milling, insight into the unique reactivity of solid-state substrates, which is often different from that in solution, has been poorly explored. In this study, we investigated the relationship between the reactivity and melting points of aryl halides in solid-state Suzuki–Miyaura cross-coupling reactions and the effect of reaction temperature on these processes. We found that aryl halides with high melting points showed significantly low reactivity in the solid-state cross-coupling near room temperature, but the reactions were notably accelerated by increasing the reaction temperature. Given that the reaction temperature is much lower than the melting points of these substrates, the acceleration effect is most likely ascribed to the weakening of the intermolecular interactions between the substrate molecules in the solid state. The present study provides important perspectives for the rational design of efficient solid-state organic transformations using ball milling.
Keywords: cross-coupling; solid state; mechanochemistry; ball milling; palladium catalyst